Oxidative defense mechanisms of proline on growth, nutritional compositions and antioxidant activities in water-stressed Solanum aethiopicum L. - Ojewumi, A. W.; Keshinro, M. O.; Mabinuori, L. F.; Makinde , S. C. O. (Journal of Plant Stress Physiology, 2023)
The growth performance of vegetables is influenced by water availability. This study explored the use of proline as an osmoregulator on growth, nutritional compositions and oxidative enzyme activities in water-stressed Solanum aethiopicum. Seedlings of the vegetable were subjected to 20, 40, 60, 80 and 100% proline against droughted and well-watered. Morphological and physiological characters, nutritional compositions and oxidative activities were determined in the vegetable. Plant height (20.37 cm), number of leaves (35.75 cm), Leaf area (347.55 m2), specific leaf area (72.02 m2 g-1), leaf area index (0.71 m2 m-2) relative growth rate (0.21 mg g-1 day-1), net assimilation rate (0.058 mg g-1 day-1) and leaf area ratio (0.19 m2 g-1) were higher in S. aethiopicum seedlings sprayed with 100% proline. Crude fat (0.11%), ash (1.57%), crude fibre (1.49%), crude protein (2.44%) and carbohydrate (3.50%) were higher in the leaves of the vegetable sprayed with 100% proline. Higher vitamin A (84.21 mg/100 g), vitamin B3 (0.56 mg/100 g) and vitamin C (10.97 mg/100 g) were observed in the leaves of the vegetable under 100% proline. Furthermore, sodium (8.93 mg/100 g), potassium (402.20 mg/100 g), calcium (121.55 mg/100 g) and magnesium (58.80 mg/100 g) were recorded in the leaves of well-watered. Higher SOD (0.88 mg g-1), APX (0.95 mg g-1), CAT (0.98 mg g-1), GR (0.96 ug g-1) and GST (14.52 mg g-1) were observed in the roots of S. aethiopicum droughted. Although all the proline levels sustained growth components, nutritional compositions and oxidative enzymes of S. aethiopicum under water stress, however, 100% proline produced better ameliorative effects.